A 3D particle model for the plume CEX simulation. (17th July 2018) - Lu, C.; Qiu, P.; Cao, Y.; Zhang, T.P.; Chen, J.J.
ABSTRACT: Charge Exchange (CEX) ion is the main factor causing the plume pollution. The distribution of CEX ions is determined by the distribution of beam ions and neutral atoms. Hence, the primary problem in the study of the plume is how to accurately simulate the distribution of beam ions and neutral atoms. At present, the most commonly used model utilised for the plume simulation is the analytical model proposed by Roy for the plume simulation of the NASA Solar Technology Application Readiness (NSTAR) ion thruster. However, this analytical model can only be applied to the ion beam with small divergence angles. In addition, the analytical model is no longer applicable to the simulation for the plume of a new type of ion thruster that appeared recently, which is called the annular ion thruster. In this paper, a 3D particle model is proposed for the plume simulation of ion thrusters consisting of the particle model for beam ions, the Direct Simulation Monte Carlo (DSMC) model for neutral atoms and the Immersed Finite Element-Particle In Cell-Monte Carlo Collision (IFE-PIC-MCC) model for CEX ions. Then, the plume of the NSTAR ion thruster is simulated by both Roy's model and the 3D particle model. The simulation results of both models are then compared with the experimental results. It is shown that the numerical results of the 3D particle model agree well with those of the analytical model and the experimental data. And this 3D particle model can also be used for other electric thrusters.